2016
DOI: 10.1007/s11605-016-3269-x
|View full text |Cite
|
Sign up to set email alerts
|

How Does Cholecystectomy Influence Recurrence of Idiopathic Acute Pancreatitis?

Abstract: BackgroundIdiopathic acute pancreatitis is diagnosed in approximately 10–30 % of cases of acute pancreatitis. While there is evidence to suggest that the cause in many of these patients is microlithiasis, this fact has not been translated into a resource efficient treatment strategy that is proven to reduce recurrence rates. The aim of this study was to examine the value of prophylactic cholecystectomy following an episode of acute pancreatitis in patients with no history of alcohol abuse and no stones found o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…In a retrospective study comparing cholecystectomy vs follow-up in patients with IAP, the recurrence of AP was lower in cholecystectomy patients compared with follow-up (14% vs 43%; p=0.003). 27 Räty et al 28 confirmed these findings in a randomised trial reporting a recurrence rate of 14/37 in the follow-up arm vs 4/35 in the cholecystectomy arm (OR 4.7, 95% CI 1.4 to 1.6, p=0.008) with a median follow-up of 24 months. Regarding sphincterotomy, Kim et al 17 showed an absence of recurrence in 87.5% of patients with bile duct stones or sludge after sphincterotomy during a 36-month follow-up period.…”
Section: Discussionmentioning
confidence: 83%
“…In a retrospective study comparing cholecystectomy vs follow-up in patients with IAP, the recurrence of AP was lower in cholecystectomy patients compared with follow-up (14% vs 43%; p=0.003). 27 Räty et al 28 confirmed these findings in a randomised trial reporting a recurrence rate of 14/37 in the follow-up arm vs 4/35 in the cholecystectomy arm (OR 4.7, 95% CI 1.4 to 1.6, p=0.008) with a median follow-up of 24 months. Regarding sphincterotomy, Kim et al 17 showed an absence of recurrence in 87.5% of patients with bile duct stones or sludge after sphincterotomy during a 36-month follow-up period.…”
Section: Discussionmentioning
confidence: 83%
“…Among the ten included studies, there was one RCT 8 , one cross-sectional study 20 , six prospective cohort studies 4,5,21 -24 and two 9,19 retrospective cohort studies (Table 1). The only RCT 8 compared cholecystectomy with conservative treatment in 85 patients with IAP, with an allocation ratio of 1 : 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of these, 23 patients were included in one case-control study 19 and were excluded from further analyses, leaving 524 patients with 'original' IAP in the meta-analysis. Six cohorts 5,19 -21,23,24 included patients with recurrent IAP, whereas three studies 4,9,22 did not report this. Only one study 8 excluded patients with a recurrent episode of 'presumed' IAP (Table 2).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations